2016
DOI: 10.1016/j.jsb.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction and assembly of Bacillus subtilis spore coat proteins CotE and CotZ studied by atomic force microscopy

Abstract: The spore of Bacillus subtilis, a dormant type of cell, is surrounded by a complex multilayered protein structure known as the coat. It is composed of over 70 proteins and essential for the spore to withstand extreme environmental conditions and allow germination under favorable conditions. However, understanding how the properties of the coat arise from the interactions among all these proteins is an important challenge. Moreover, many specific protein-protein interactions among the coat proteins are crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…As demonstrated, the morphogenetic protein CotE interacted directly and specifically with CotZ, resulting in the formation of a stable complex, and this phenomenon was strongly dependent on the CotE/CotZ ratio. Importantly, the above results not only provided crucial information on spore cote assembly, which might be translated into the design of improved sporicidal agents, but also confirmed unique advantages of the AFM/SMFS analysis for characterization of other coat proteins [150].…”
Section: Investigation Of Bacteria and Fungi Phenotypic And Virulence Features Using Afmsupporting
confidence: 56%
See 1 more Smart Citation
“…As demonstrated, the morphogenetic protein CotE interacted directly and specifically with CotZ, resulting in the formation of a stable complex, and this phenomenon was strongly dependent on the CotE/CotZ ratio. Importantly, the above results not only provided crucial information on spore cote assembly, which might be translated into the design of improved sporicidal agents, but also confirmed unique advantages of the AFM/SMFS analysis for characterization of other coat proteins [150].…”
Section: Investigation Of Bacteria and Fungi Phenotypic And Virulence Features Using Afmsupporting
confidence: 56%
“…Regarding the investigation of bacterial spore structure and functioning, a particularly interesting study was performed by Liu and co-workers [150]. The authors engaged AFM-based SMFS to investigate the specific interactions between B. subtilis spore's coat proteins, determining the spores' resistance to unfavorable environmental conditions and analyzing both unbinding force and kinetic data in CotE and CotZ proteins.…”
Section: Investigation Of Bacteria and Fungi Phenotypic And Virulence Features Using Afmmentioning
confidence: 99%
“…Surrounding the cortex, the spore coat consists of about 80 proteins deposited by the mother cell arranged in inner and outer layers ( Fig. 3) (Liu et al 2016;McKenney et al 2013).…”
Section: Structure Of B Subtilis Sporesmentioning
confidence: 99%
“…Several studies demonstrated that morphogenetic proteins are in direct contact, indicating that they could form a basic, foundational structure, a scaffold to which the coat proteins are attached as the process of spore coat formation proceeds [15][16][17][18][19]. Other coat proteins are also produced at the same time as the key morphogenetic proteins, all of which are under the control of σ E .…”
Section: Introductionmentioning
confidence: 99%